UV sources and plastic composition influence microplastic surface degradation: Implications for plastic weathering studies - Burrows, Stephen; Colwell, John; Costanzo, Sarah; Kaserzon, Sarit; Okoffo, Elvis; Ribeiro, Francisca; O'Brien, Stacey; Toapanta, Tania; Rauert, Cassandra; Thomas, Kevin V; Galloway, Tamara (Journal of hazardous materials advances, 2024)
•UV light source, polymer type and additive content all impacted surface weathering.•Evidence suggests surface roughness may have influenced photooxidation via shading.•Carbonyl index must be used with caution when estimating duration of photooxidation.•Characterising microplastic additives is key to understanding weathering pathways. Microplastic surface properties are dynamic in the environment, as weathering, primarily through photooxidation due to ultraviolet light (UV) exposure, modifies surface chemistry and surface roughness, which can affect the fate, transport and reactivity of microplastics, and therefore any potential environmental risk they may pose. This study aims to investigate and characterise the effect of different UV radiation sources that are typically used in weathering studies (UVA-340 fluorescent lamps, xenon-arc lamps and natural sunlight) on two key properties of microplastics: surface roughness and oxidation level. High- and low-density polyethylene, polypropylene and polystyrene microplastic nurdles (<5 mm) were weathered and characterised using Atomic Force Microscopy and Fourier-Transform Infrared spectroscopy. After two weeks, UVA light was found to significantly increase the carbonyl index of the subject high-density polyethylene and decrease its surface roughness. The subject low-density polyethylene was found to increase in carbonyl index when exposed to all three light sources for two weeks, and reduced in surface roughness when exposed to both xenon-arc and UVA light. Xenon-arc light increased surface roughness on the subject polypropylene after two weeks exposure. The subject polystyrene significantly increased in carbonyl index when exposed to xenon-arc light for two weeks but decreased in surface roughness when exposed to UVA light. Surface oxidation was found to be dependent on polymer type, UV source and additive content, with the data showing a relationship between surface roughness, surface shading and additive content. The results from this study highlight the complexity of microplastic weathering processes and how metrics such as carbonyl index must be applied with caution when estimating how long a plastic has been in the environment. [Display omitted]